Back Cover: Modular Assembly of Allosteric MEK Inhibitor Structural Elements Unravels Potency and Feedback‐Modulation Handles (ChemMedChem 12/2015). Issue 12 (December 2015) - Hartung, Ingo V.; Pühler, Florian; Neuhaus, Roland; Scholz, Arne; Siemeister, Gerhard; Geisler, Jens; Hillig, Roman C.; von Ahsen, Oliver; Hitchcock, Marion
Abstract : The back cover picture shows our modular approach in reassembling previously described building blocks of inhibitors for the mitogen‐activated protein kinase kinase (MEK). We have combined our recently identified C6‐phenoxy side chains with cores derived from two MEK inhibitors that are currently in clinical development. This modular approach has allowed us to synthesize and characterize two novel series of highly potent allosteric MEK inhibitors. We report their pharmacokinetic properties and in vivo efficacy data for one advanced preclinical candidate. Inspection of effects of these new inhibitors on MEK phosphorylation allowed us to further unravel structural intricacies of MEK–Raf feedback interactions. More details can be found in the Full Paper by Ingo V. Hartung, Marion Hitchcock et al. onpage 2004 in Issue 12, 2015 (DOI:10.1002/cmdc.201500442 ).